The Model of the Student Governance Council Management in School under Surat Thani Provincial Administrative Organization - Malitip, Harinrat; Yotharak, Maliwan; Tippamas, Wanchat; Sookkaew, Chaturong (Academic MCU Buriram Journal, 2021)
The objectives of this research are as follows: 1) To study the state of administration of student council in school. 2) To study the model of student good governance council. 3) to present the model for administration of student good governance council in school under Surat Thani provincial administrative organization, The key informants composed of administrators, teachers, primary education committee and agents of parents, to study of documentaries and concerned researches and in depth interview, and focus group discussion. The instrument for data collection was interview form and agenda of focus group. The research result finds that: 1) The state of administration of student council depend upon the background of each school, under principle, concept and origination as the i.e. for the activity performance of students and learning about democracy regime under the King as the head. 2) The model for administration of student council is the student council that having more duty as the court with reconciliation or helping student in the case of quarrel or losing marks of good character or any others. 3) The model for administration composed of structure as participation from variety of section committee and advisers i.e. administrator, teacher, agent of school board committee and agent of parents according to SBMLD ( School Based Management For Local Development) it means administration based on school for local development under fight information and advice, the student good governance performed under Deming circle (PDCA) i.e. Plan, Do Check and Act. With applying the six aspects of good governance i.e. lawful, virtue, transparency, participation, responsibility and valuable as the accordance with and benefit able.